Q. 975.0( 1 Vote )

<span lang="EN-US

Answer :

False

If AB = AC => B=C


The above condition is only possible if matrix A is invertible


(i.e |A|≠0).


If A is invertible, then


A-1(AB)= A-1(AC)


(A-1A)B = (A-1A)C


IB=IC


B=C


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-USMathematics - Exemplar

<span lang="EN-USMathematics - Exemplar

Using matrices soMathematics - Board Papers

On her birthday SMathematics - Board Papers

Using matrices soMathematics - Board Papers

<span lang="EN-USRS Aggarwal - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

Using elementary RS Aggarwal - Mathematics

Using elementary RS Aggarwal - Mathematics